2005
DOI: 10.1039/b506289f
|View full text |Cite
|
Sign up to set email alerts
|

On-line coupling of a microelectrode array equipped poly(dimethylsiloxane) microchip with an integrated graphite electrospray emitter for electrospray ionisation mass spectrometry

Abstract: A novel method for the manufacturing of microchips for on-chip combinations of electrochemistry (EC) and sheathless electrospray ionisation mass spectrometry (ESI-MS) is described. The technique, which does not require access to clean-room facilities, is based on the incorporation of an array of gold microcoil electrodes into a poly(dimethylsiloxane)(PDMS) microflow channel equipped with an integrated graphite based sheathless ESI emitter. Electrochemical measurements, which were employed to determine the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…The latter can be accomplished using sufficiently long transfer lines ($30 cm) between the electrochemical cell and the mass spectrometer [6,17], the insertion of a ground point prior to the ESI-MS system [20][21][22][23][40][41][42][43][44] or by allowing the whole EC-ESI-MS system to float on the potential induced by the ESI high voltage, as described by Cole and co-workers [7,8], Nyholm and co-workers [27,28,[45][46][47], and Van Berkel et al [48]. The main disadvantage with the use of a long transfer line is the increased transfer time between the flow cell and the ion source which makes the detection of unstable electrochemical reaction products difficult.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter can be accomplished using sufficiently long transfer lines ($30 cm) between the electrochemical cell and the mass spectrometer [6,17], the insertion of a ground point prior to the ESI-MS system [20][21][22][23][40][41][42][43][44] or by allowing the whole EC-ESI-MS system to float on the potential induced by the ESI high voltage, as described by Cole and co-workers [7,8], Nyholm and co-workers [27,28,[45][46][47], and Van Berkel et al [48]. The main disadvantage with the use of a long transfer line is the increased transfer time between the flow cell and the ion source which makes the detection of unstable electrochemical reaction products difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been demonstrated that the electrochemical reactions in the electrospray can be used to oxidise or reduce species in the solution or the electrospray capillary itself [7,41,42,50,51], it is generally difficult to utilise this approach for the present purposes as the electrochemical potential of the spray capillary is determined by the magnitude of the electrospray current, the capillary material and the concentrations of the available electroactive species in the solution [26]. The most appropriate way to decouple the electrochemical cell from the ESI high voltage is consequently to allow the EC system to float on the potential induced by the ESI high voltage either by using a battery-operated potentiostat [7,8,47] or an isolation transformer [27,28,46,48]. The main draw back with this approach is the hazard associated with the use of a (high voltage) floating system, which is why particular care needs to be taken when employing such EC-ESI-MS systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different approaches have been published in the past 7 years with complete references available in the review articles. Some of the latest attempts include systems integrating the ESI ionization nozzle in devices fabricated in polydimethylsiloxane (PDMS) [53,54]. The use of casting technologies is quite popular for rapid laboratory replications and prototyping.…”
Section: Systems For High-throughput Separationsmentioning
confidence: 99%
“…ESI has been obtained directly from the PDMS bulk, either by applying the potential upstream [16][17][18][19][20][21], or by using a sheathless design [15]. The use of sheathless electrospray enables electrophoretic separation before electrospray without any interaction between the electrode and the eluting analytes.…”
Section: Introductionmentioning
confidence: 99%